A caching‐enabled light control scheme for aerobics video. Issue 5 (25th January 2021) - Qi, Ting
Abstract : The video transmission traffic has account for 60% Internet traffic, and how to optimize the video transmission efficiency has become a major challenge. Especially, the aerobics video is strongly subjected to both temporal locality and spatial locality, and the related contents are also dynamically changeable with the precise and complex movements. Thus, in the age of multimedia, the transmission optimization of aerobics video has the considerable research value. In this paper, a transmission control scheme for aerobics video is proposed. This scheme has the light feature, which is embodied by one heuristic video compression method. Then, this paper realizes the effective congestion control based on the adaptive rate design. Meanwhile, video compression and congestion control are performed in the simultaneous way, and they are completed by using the explored in‐network cache. Given this, the simple cache allocation method is presented at last. Two baselines are compared by evaluating packet loss rate, transmission time and delay jitter, and the experiment results demonstrate the efficiency of the proposed transmission scheme. Abstract : Video compression module and transmission control module work in the simultaneous way. In addition, they are connected by the caching‐enabled ICN router, where the part of cache space is used to support the computation of video compression and the remaining cache space is used to provide the buffering function for transmission control.